Community-level changes in condom use and uptake of HIV pre-exposure prophylaxis by gay and bisexual men in Melbourne and Sydney, Australia: results of repeated behavioural surveillance in 2013–17. Issue 8 (August 2018) - Holt, Martin; Lea, Toby; Mao, Limin; Kolstee, Johann; Zablotska, Iryna; Duck, Tim; Allan, Brent; West, Michael; Lee, Evelyn; Hull, Peter; Grulich, Andrew; De Wit, John; et al.
Summary: Background: Pre-exposure prophylaxis (PrEP) has been rapidly rolled out in large, publicly funded implementation projects in Victoria and New South Wales, Australia. Using behavioural surveillance of gay and bisexual men, we analysed the uptake and effect of PrEP, particularly on condom use by gay and bisexual men not using PrEP. Methods: We collected data from the Melbourne and Sydney Gay Community Periodic Surveys (GCPS), cross-sectional surveys of adult gay and bisexual men in Melbourne, VIC, and Sydney, NSW. Recruitment occurred at gay venues or events and online. Eligible participants were 18 years or older (face-to-face recruitment) or 16 years or older (online recruitment), identified as male (including transgender participants who identified as male); and having had sex with a man in the past 5 years or identified as gay or bisexual, or both. Using multivariate logistic regression, we assessed trends in condom use, condomless anal intercourse with casual partners (CAIC), and PrEP use by gay and bisexual men, controlling for sample variation over time. Findings: Between Jan 1, 2013, and March 31, 2017, 27 011 participants completed questionnaires in the Melbourne (n=13 051) and Sydney (n=13 960) GCPS. 16 827 reported sex with casual male partners in the 6 months before survey and were included in these analyses. In 2013, 26 (1%) of 2692 men reported CAIC and were HIV-negative and using PrEP, compared with 167 (5%) of 3660 men in 2016 and 652 (16%) of 4018 men in 2017 (p<0·0001). Consistent condom use was reported by 1360 (46%) of 2692 men in 2013, 1523 (42%) of 3660 men in 2016, and 1229 (31%) of 4018 men in 2017 (p<0·0001). In 2013, 800 (30%) of 2692 men who were HIV-negative or untested and not on PrEP reported CAIC, compared with 1118 (31%) of 3660 men in 2016, and 1166 (29%) of 4018 in 2017 (non-significant trend). Interpretation: A rapid increase in PrEP use by gay and bisexual men in Melbourne and Sydney was accompanied by an equally rapid decrease in consistent condom use. Other jurisdictions should consider the potential for community-level increases in CAIC when modelling the introduction of PrEP and in monitoring its effect. Funding: Australian Government Department of Health, Victorian Department of Health and Human Services, and New South Wales Ministry of Health.